HRCT evaluation of patients with interstitial lung disease: comparison of the 2018 and 2011 diagnostic guidelines. (October 2020) - Nathan, Steven D.; Pastre, Jean; Ksovreli, Inga; Barnett, Scott; King, Christopher; Aryal, Shambhu; Ahmad, Kareem; Fukuda, Cesar; Ramalingam, Vijaya; Chung, Jonathan H.
Background and aims: Chest high-resolution computed tomography (HRCT) is the central diagnostic tool in discerning idiopathic pulmonary fibrosis (IPF) from other interstitial lung disease (ILDs). In 2018, new guidelines were published and the nomenclature for HRCT interpretation was changed. We sought to evaluate how clinicians' interpretation would change based on reading HRCTs under the framework of the old versus new categorization. Materials and methods: We collated HRCTs from 50 random cases evaluated in the Inova Fairfax ILD clinic. Six ILD experts were provided the deidentified HRCTs. They were all instructed to independently provide two reads of each HRCT, based on the old and the new guidelines. Results: The kappa statistic for concordance for HRCT reads under old guidelines was 0.5, while for the new guidelines it was 0.38. Under the framework of the old guidelines, there were 22 HRCTs with unanimous consensus reads, while only 15 with the new guidelines. There were 12 HRCTs read unanimously as usual interstitial pneumonia (UIP) pattern based on both the old and the new guidelines. Ten HRCTs were read as a possible UIP pattern based on the old guidelines and were classified in nine cases as probable UIP and one indeterminate based on the new guidelines. Of the 28 inconsistent UIP HRCTs (old guidelines), 25 were read as alternative diagnosis suggested, two were read as indeterminate and one as probable UIP. Conclusion: Implementation of the new guidelines to categorize HRCTs in ILD patients appears to be associated with greater inter-interpreter variability. How or whether new guidelines improve the care and management of ILD patients remains unclear. The reviews of this paper are available via the supplemental material section.